Network Governance of Mental Health Services for Sexual Violence Victims in Surakarta - Jacika Pifi Nugraheni; Joko Pramono; Wirid Winduro (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Sexual violence has long-term consequences for victims’ mental health, including post-traumatic stress disorder (PTSD), depression, anxiety, and a diminished sense of safety. This study analyzes the governance of mental health services for victims of sexual violence in Surakarta City using network governance and social capital perspectives. A qualitative approach was employed through in-depth interviews with survivors, community-based companions, and local service providers, supported by document review and observation.The findings show that psychosocial recovery is mainly facilitated through non-governmental networks perceived as more responsive and victim-centered, particularly via community-based counseling, peer support, and psychoeducational initiatives. In contrast, formal services provided by the local government through DP3AP2KB, including PUSPAGA and the PIK-R network, have not functioned optimally as referral hubs for mental health recovery, especially for adult victims. This condition is related to an administrative service orientation, a preventive focus, and the absence of integrated referral mechanisms linking government, community, and health services. Recovery is strongly supported by bonding and bridging social capital, while linking social capital remains weak due to limited institutionalized cross-sector collaboration. Strengthening network-based governance through the integration of PUSPAGA, PIK-R, and community companions is essential to expanding access to victim-centered mental health services.